Research on biomechanical analysis of football player using information technology in sports field - Ali Zaib; Muhammad Talal Ahmad (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The basic aim of this research study is to measure the research related to the biomechanical analysis of football players using information technology in the sports field. This research study depends upon questions related to the biomechanical analysis of football players and information technology. This research study depends upon primary data analysis to determine the research used questions related to biomechanical analysis and information technology. For measuring, the research study used the software of smart PLS and generated informative results, including the smart PLS Algorithm model. The indicator correlation, significant analysis, and total effect present the research between them. The biomechanical analysis of football players is the main independent variable, and information technology is the dependent variable. The football players, coaches, and every person related to sport industries are considered as research participants. The overall research found that the biomechanical analysis of football player positively affects by using of information technology. Information technology shows a significant impact on the biomechanical analysis of football player. Information technology plays an informative role in the biomechanical analysis in football players activities.